2017
DOI: 10.1177/2057178x17698481
|View full text |Cite
|
Sign up to set email alerts
|

The motogenic effect of EGF and TGF-α on the migration of tumor cells from the oral region

Abstract: Aim: Epithelial-to-mesenchymal transition (EMT) is recognized as a hallmark of cancer. The change in phenotype of epithelial cells enables them to migrate and the cancer therefore, to become more aggressive. The presence of the epidermal growth factor receptor (EGFR) has been implicated in the spread and aggressive nature of oral tumors. The aims of this present study were to investigate the role of two different growth factors, both ligands of the receptor, and their influence on EMT and cellular motility.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Cell scattering is a dynamic process for investigating EMT in which dispersion of compact colonies of epithelial cells is induced by certain soluble factors such as growth factors [20]. The assay was performed as described earlier [10]. In brief, cells were seeded at a density of 2 × 10 4 cells/ml, in 60 mm dishes and grown until small well-defined colonies were visible.…”
Section: Scatter Assay and Immunofluorescent Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell scattering is a dynamic process for investigating EMT in which dispersion of compact colonies of epithelial cells is induced by certain soluble factors such as growth factors [20]. The assay was performed as described earlier [10]. In brief, cells were seeded at a density of 2 × 10 4 cells/ml, in 60 mm dishes and grown until small well-defined colonies were visible.…”
Section: Scatter Assay and Immunofluorescent Stainingmentioning
confidence: 99%
“…We have previously shown that the PI3 kinase/Akt pathways are essential for the migration of fibroblasts and oral cancer cells in response to added factors. The addition of PI3 kinase/Akt inhibitors block the migration stimulating activity of VEGF, EGF and TGFα, the data indicating that those growth factors increase phosphorylation of Akt at Thr 308 and Ser 473 [8][9][10]. The role of TGFβ1, however, is still unknown in oral cancer cell metastasis.…”
Section: Introductionmentioning
confidence: 99%